Modelling and Design of Photovoltaic Fed Re-lift Luo Converter for Air Conditioner - Ali, Shajith; Venthan, Ezhil (Applications of Modelling and Simulation, 2019)
The design of high gain converter with photovoltaic (PV) module is carried out in this paper for air conditioning application. The solar based power system gaining large importance due to the renewable nature and increased life time. To understand power and voltage characteristic of PV module, the five parameter single diode model is evolved and analyzed. Due to the varying power characteristic of PV panel to the temperature and irradiance change, perturb and observe maximum power point tracking algorithm is imposed to harvest the maximal potential PV power. Air conditioner require high currents so solar modules are connected in parallel instead of series configuration. Since the output voltage of PV module is low, it requires a DC to DC power electronic converter with large voltage gain to boost the output voltage. Various converters such as conventional boost, buck/boost and Luo converters to provide high voltage gain are analyzed in this work and Luo converter is found to give small ripple in current and voltage as compared to the other two converters for the same voltage gain. Further, in Luo converter, voltage gain can be improved by lifting technique in which self-lift and re-lift techniques are employed. The Re-lift Luo converter has high voltage gains twice that of self-lift Luo and reduced ripple for solar power application. For air conditioning application AC output is obtained using a full bridge single phase voltage source inverter.